Controversies in cough management: An Indian perspective - Dhanya Mohan (Wolters Kluwer Medknow Publications, 2019)
Chronic cough is one of the most common symptoms for patients-seeking consultation in an outpatient clinic. It is associated with substantial psychological, physical, and social burdens and impaired quality of life. This review highlights some of the major diagnostic and management challenges confronted in the field of cough with a special focus on the Indian perspective. Heterogeneity in definitions and classifications and challenges associated with over-the-counter drug use and irrational drug use are some of the major controversies. Streamlined diagnostic approach involving a combination of subjective and objective tools, evidence-based amendments in clinical practice, and stringent implementation of regulatory guidelines are mandatory to address controversies in cough management in developing countries.